The Ilima-Letsema programme's contribution to poverty alleviation in Gauteng Province, South Africa - Nkgudi, Tshidi Mokgadi; Maake, Matome Moshobane Simeon; Masekoameng, Mosima Rachel (Frontiers in Sustainable Food Systems, 2022)
The South African government initiated the Ilima-Letsema programme to promote sustainable agricultural activities and improve the livelihoods of households in farming communities. The purpose of the paper is to evaluate the Ilima-Letsema programme’s contribution to job creation and poverty alleviation in the Midvaal Local Municipality of Gauteng Province, South Africa. The quantitative research approach and survey design were used to conduct the study. Data were collected from 196 beneficiaries of the programme through face-to-face interviews using structured questionnaires. The Statistical Package for the Social Sciences (SPSS) version 27 was used to analyse the data whereby descriptive statistics, T-test, Cochran’s Q and McNemar tests were employed. The results indicated that the Ilima-Letsema programme significantly increased farmers' income and created jobs. In addition, the programme significantly uplifted the elite beneficiaries from the upper-bound poverty line (UPBL) to better livelihoods. However, the support provided by the programme did not uplift poor farmers from the food poverty line (FPL) and lower bound poverty line (LBPL). Education, farmland size and income had a positive and significant correlation (p<0.05) with the programme’s ability to uplift the beneficiaries from FPL, UBPL and UPBL amounts. It is recommended that the government should increase the budget allocated to the Ilima-Letsema programme and make it accessible to most farmers to increase net farm income and create jobs. In addition, the programme should provide more support to resource-poor farmers and encourage beneficiaries to acquire more education and increase their farmland.